Engineering of Perovskite Oxides for Electrochemical Water Splitting - Xu, Xiaomin (Curtin University, 2020)
While electrochemical water splitting offers an alluring prospect of carbon-neutral H₂ production from renewable resources, its efficiency is limited by the slow kinetics of the anodic/cathodic half-reactions. This thesis centres on the engineering of non-precious metal-based perovskite oxides as electrocatalysts to drive the water electrolysis. By fine-tuning the chemical compositions and structures, perovskite oxides with improved catalytic efficiency are developed. A deepened understanding of the structure–activity relationship of the perovskite electrocatalysts is also provided.